2011
DOI: 10.1089/pop.2010.0060
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Success Zone: You Auto Know A Worksite-Based Program to Improve Blood Pressure Control Among Auto Workers

Abstract: Worksite-based wellness programs can be a means to improve employee health awareness and potentially reduce health care costs. The "BP Success Zone: You Auto Know" program was a worksite-based intervention to reduce the incidence of hypertension among auto workers at Chrysler LLC. This 6-month program comprised an intervention consisting of education, awareness, and support intended to intensify the engagement of Chrysler employees at moderate-to-high cardiovascular risk who were not adequately controlling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Occupational health nurses have long been involved in case management, lifestyle behavior change programs (e.g., smoking cessation and weight management), and risk factor identification, whether the risk factors are due to work, personal lifestyle choices, family history, or genetics. Studies show the effectiveness of a variety of worksite health promotion interventions, many of which involve occupational health nurses (Jackson et al, 2011;Mauceri et al, 2011;Pelletier, 2009;White & Jacques, 2007). Yap, Davis, Gates, Hemmings, and Pan (2009a) studied tailored e-mail messages sent weekly by occupational health nurses for 6 weeks to encourage physical activity among manufacturing employees who were contemplating or preparing for behavior change.…”
Section: Health Improvementmentioning
confidence: 99%
“…Occupational health nurses have long been involved in case management, lifestyle behavior change programs (e.g., smoking cessation and weight management), and risk factor identification, whether the risk factors are due to work, personal lifestyle choices, family history, or genetics. Studies show the effectiveness of a variety of worksite health promotion interventions, many of which involve occupational health nurses (Jackson et al, 2011;Mauceri et al, 2011;Pelletier, 2009;White & Jacques, 2007). Yap, Davis, Gates, Hemmings, and Pan (2009a) studied tailored e-mail messages sent weekly by occupational health nurses for 6 weeks to encourage physical activity among manufacturing employees who were contemplating or preparing for behavior change.…”
Section: Health Improvementmentioning
confidence: 99%
“… 11 Jackson et al reported that there was a decline in blood pressure and an increased level of awareness among the workers after the interventions through health education for 6 months (86%). 12 Merrill et al compared the employees of Lincoln Industries with those outside Lincoln Industries in terms of four wellness indicators, namely emotional health, physical health, access to health‐related services, and engagement in healthy behaviors. 13 It was found that the employees of the Lincoln Industries were better than those outside in three of the four indicators, namely emotional health, physical health, and engagement in healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Byrne et al presented the findings of their seven‐year research (2003–2009) at Vanderbilt University, in which the application of health promotion programs had improved the physical activities of employees from 73% to 83% 11 . Jackson et al reported that there was a decline in blood pressure and an increased level of awareness among the workers after the interventions through health education for 6 months (86%) 12 . Merrill et al compared the employees of Lincoln Industries with those outside Lincoln Industries in terms of four wellness indicators, namely emotional health, physical health, access to health‐related services, and engagement in healthy behaviors 13 .…”
Section: Introductionmentioning
confidence: 99%